IMPLEMENTASI PERKEMBANGAN TEKNOLOGI PEMASARAN PRODUK PADA UMKM DI KOTA BATAM - Putri Yuni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
This scientific article contains briefly on the topic of humanity and the application of action. This scientific article contains a briefly about the discussion on the digital revolution in the era of technology 4.0 and the application of technological elements in the business community. The dynamics of the digital revolution continue especially in the use of business processes and marketing. The use of digital technology can help to gain market share through promotion on platforms that provide a platform for business. This article explains the details of the initial design process for implementing a business model using social media platforms. Amid the Covid-19 pandemic, it is expected to be able to help MSME entrepreneurs to continue to gain market with this online network. Further discussion will be explained in this article.